Environmental Attitude dengan Science Process Skills Sekolah Dasar - shofiyah, Tsaniyatus; Apri Irianto; Reza Rachmadtullah (EDUPEDIA Publisher, 2023)
Science process skills are important to teach to students because they can create meaningful learning. To be able to create a learning environment that facilitates science process skills, learning must involve aspects contained in science process skills. However, in science school, student process skills still involve aspects of observation while other aspects such as classifying, predicting, and communicating are still not applied. So students are still not actively involved in science process skills. Efforts can be done by involving direct experience in the form of students' environmental attitudes. Therefore, the purpose of this study is to determine the relationship between environmental attitude and science process skills in elementary schools. This study used quantitative methods with a correlational approach. The sample of this study amounted to 36 students. Data collection is carried out through questionnaires, tests, and observations. The data were analyzed using a normality test, linearity test, and hypothesis test. The results of this study obtained a relationship between environmental attitude and science process skills in elementary schools. The relationship is quite strong, which means that the higher the students' environmental attitude towards environmental care and awareness, the higher the behavior and science process skills. Conversely, if students' environmental attitudes towards environmental care and environmental awareness are low, then behavior and science processing skills are also low.